Rams Little Dodeon in GUL, MS Ferguson 7 (FF. 48V-58V): a Semi-Diplomatic Edition - Lorente-Sánchez, Juan (Universidad de Málaga, 2023)
The present paper offers an edition of a handwritten version of Rams Little Dodeon housed in GUL, MS Ferguson 7 (ff. 48v-58v), an up-to-now unedited Early Modern English volume kept in the Archives and Special Collections Department of the University of Glasgow. The principles of a semi-diplomatic transcription have been followed in order to provide the reader with the most accurate reproduction of the original witness, as the degree of editorial intervention has been kept to a minimum. Thus, the edition may be conceived as an appropriate input for diverse research areas such as historical linguistics, manuscript studies, textual criticism and the history of medicine, among others. Finally, a glossary accompanies the edition for the sake of a good understanding of the concepts included in it.
Rams Little Dodeon en el MS Ferguson 7 (ff. 48v-58v) de la Biblioteca de la Universidad de Glasgow: una edición semidiplomática
Keywords: Manuscritos ingleses - Edición; Inglés moderno; Semi-diplomatic edition; Edition; Manuscripts; Early Modern English; Rams Little Dodeon; MS Ferguson 7